PECULIARITIES OF FORMATION OF ACCOUNTING OF PRODUCTS AND SERVICES OF ENOTOURISM AS A COMPONENT OF THE PERFORMANCE OF WINERIES - MARCHUK, Uliana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article outlines the peculiarities of developing enotourism (wine tourism) in Ukraine as a type of gastronomic tourism. The accounting system’s adaptation processes to reflect the services provided are indicated. Attention is focused on the place of gastronomic tourism among unusual types of tourism. The factors influencing the accounting of gastronomic tourism wineries are outlined. The place of enotourism among the categories of gastronomic tourism is determined, and its main forms are highlighted: excursion to vineyards and wineries; enogastronomic dinner; a master class in enogastronomy; wine tasting with a lecture by an experienced sommelier; visiting wine festivals and exhibitions; comprehensive wine tour, etc. The article presents a study on sustainable wine tourism based on an online survey conducted in 2021 with the participation of 1579 wineries from more than 40 countries. The unique costs of enotourism are highlighted, particularly costs associated with a new accounting object and requiring changes to its accounts, cost systems (capitalization of vineyard costs, depletion allowances, and allocation of costs for exported goods), and many other procedures. The author analyzes the effects of the war on the wine industry. The wineries and warehouses in different regions of Ukraine that suffered as a result of Russia’s full-scale invasion are listed. The article presents the views of scientists on the peculiarities of accounting for wine tourism in Ukraine, in particular, the accounting for specific costs associated with the provision of enotourism services by individual items, the formation of income from the sale of services, the formation of the cost of a tourist product and their impact on the financial performance of a winery. The formation of the accounting policy of the enterprise with the allocation of separate areas that will provide features of the reflection of income from enotourism (sale of wine; tourist services, in particular: excursions, sale of souvenirs; gastronomic events, in particular: tastings, dinner, master classes, etc.) The peculiarities of reflecting in the accounting policy the items of expenses for organizing the provision of tourist services (preparation of premises, personnel, logistics, advertising) and specific expenses (for maintaining tourist infrastructure, in particular: tasting rooms and enogastronomic banquets; winemaking museums; landscape works, etc.)